Drivers of antimicrobial resistance in pig production systems of Uganda - Adrian Muwonge; Tadeo Kakooza; Paul C. D. Johnson; Lawrence Kisuule; Michael Kimaanga; Clovice Kankya; Barend Mark de Clare Bronsvoort; Tiziana Lembo (Communications Earth & Environment)
Abstract Increasing protein demand in low- and middle-income countries may accelerate livestock intensification, antibiotic overuse and antimicrobial resistance (AMR) risk. Here, we examined Uganda’s growing pig sector, tracking 70 farmers and their pigs in semi-intensive and free-range systems for a year. We investigated AMR and AMR gene abundance of 668 Escherichia coli, Klebsiella and DNA isolated from 877 faecal samples using diffusion disc-method and qPCR, respectively. Pigs in semi-intensive systems were 2.2 times more likely to exhibit AMR and had higher ermB levels. AMR in free-range farmers was twice that of pigs but still 1.4 times less likely than in semi-intensive systems. AMR prevalence increased by 0.76% per month. Potential transmission events were more likely on semi-intensive farms (OR = 3.16, 95% CI: 2.1–4.3, P < 0.001), especially when farmers had higher tetQ levels than pigs; the reverse was true for ermB. Intensified urban pig production may elevate AMR risks, underscoring the need for targeted interventions.